Nanoarchitectonics with cetrimonium bromide on metal nanoparticles for linker-free detection of toxic metal ions and catalytic degradation of 4-nitrophenol - Akash Kumar; Raja Gopal Rayavarapu (Beilstein Journal of Nanotechnology)
Heavy metal ions and organic pollutants, such as 4-nitrophenol (4-NP), pose significant environmental and human health threats. Addressing these challenges necessitates using advanced nanoparticle-based systems capable of efficient detection and degradation. However, conventional approaches utilizing strong capping agents like cetrimonium bromide (CTAB) on nanoparticles lead to limitations due to the rigid nature of CTAB. This restricts its utility in heavy metal detection and 4-NP degradation, requiring additional surface modifications using linker molecules, thereby increasing process complexity and cost. To overcome these limitations, there is a critical need for the development of an easy-to-use, dual-functional, linker-free nanosystem capable of simultaneous detection of heavy metals and efficient degradation of 4-NP. For enabling linker-free/ligand-free detection of heavy metal ions and catalytic degradation of 4-NP, CTAB was engineered as a versatile capping agent on gold and silver nanoparticles. Various factors, including nanoparticle characteristics such as shape, size, metal composition, centrifugation, and NaOH amount, were investigated for their impact on the performance of CTAB-capped nanoparticles in heavy metal detection and 4-NP degradation. CTAB-Au nanospheres demonstrated limited heavy metal ion detection capability but exhibited remarkable efficiency in degrading 94.37% of 4-NP within 1 min. In contrast, silver nanospheres effectively detected Hg2+, Cu2+, and Fe3+ at concentrations as low as 1 ppm and degraded 90.78% of 4-NP within 30 min. Moreover, anisotropic gold nanorods (CTAB-AuNR1 and CTAB-AuNR2) showed promising sensing capabilities towards Cu2+, Cr3+, and Hg2+ at 0.5 OD, while efficiently degrading 4-NP within 5 min at 1 OD. This study emphasizes the importance of tailoring parameters of CTAB-capped nanoparticles for specific sensing and catalytic applications, offering potential solutions for environmental remediation and human health protection.